2009
DOI: 10.1159/000200930
|View full text |Cite
|
Sign up to set email alerts
|

Age at Onset of Bilateral Breast Cancer, the Presence of Hereditary <i>BRCA1, BRCA2, CHEK2</i> Gene Mutations and Positive Family History of Cancer

Abstract: Background: Our research focused on the relations between the age at onset of bilateral breast cancer and the prevalence of selected hereditary BRCA1, BRCA2 and CHEK2 gene mutations with reference to their positive family history of cancer. Methods: The DNA of peripheral blood lymphocytes of patients was examined for the presence of selected hereditary mutations in the BRCA1, BRCA2 and CHEK2 genes, using molecular biology techniques. The family history of neoplasms was also analyzed. Results: The following mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Overall, our study identified 19 ATM mutation carriers with 24 breast tumors and 17 CHEK2 mutation carriers with 22 breast tumors. Median age at first BC onset was 46.9 years for ATM and 46.1 years for CHEK2 , in keeping with the literature [ 44 ]. Moreover, a high rate of bilateral tumors was observed in ATM (26.3%) and CHEK2 mutation carriers (41.2%).…”
Section: Discussionsupporting
confidence: 86%
“…Overall, our study identified 19 ATM mutation carriers with 24 breast tumors and 17 CHEK2 mutation carriers with 22 breast tumors. Median age at first BC onset was 46.9 years for ATM and 46.1 years for CHEK2 , in keeping with the literature [ 44 ]. Moreover, a high rate of bilateral tumors was observed in ATM (26.3%) and CHEK2 mutation carriers (41.2%).…”
Section: Discussionsupporting
confidence: 86%
“…We selected 12 mutations for this study from a series of 30 recurrent (seen in two or more cases) mutations of BRCA1 and BRCA2 reported in the literature in Polish women with breast or ovarian cancer to date . Seven BRCA1 mutations were selected (C61G, 185delAG, 3819del5, 3875del4, 4153delA, 5370C>T, 5382insC); each of these was previously reported in 11 or more unrelated Polish women.…”
Section: Methodsmentioning
confidence: 99%
“…Since the original study, over 50 other mutations in BRCA1 or BRCA2 have been detected in one or more breast or ovarian cancer patients from Poland, 30 of these mutations have been reported two or more times (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). It is of interest to establish if, among these additional mutations, any are sufficiently common to be introduced into an extended screening panel and thereby improve the sensitivity of our screening assay.…”
mentioning
confidence: 99%
“…Genomic DNA from peripheral blood leukocytes was obtained by phenol–chloroform extraction and analyzed by polymerase chain reaction and restriction enzyme digestion (PCR–RFLP) assays for RAD51 / G135C (rs1801320), ATM / P1054R (also known as 3161C > G, rs1800057), and CHEK2 / T470C (rs17879961) polymorphisms according to previous publications (Skasko et al 2009 ; Green and Sambrook 2012 ; Schumacher et al 2018 ). The PCR reactions were carried out in the VeritiVR Thermal Cycler (Applied Biosystems) and were done using 50–200 ng of genomic DNA, 0.4 µM of each primer, 1 × PCR buffer, 250 µM of dNTPs, 1.5 mM of MgCl 2 , and 1–2.5 units of Taq polymerase in a 50 µL reaction volume.…”
Section: Methodsmentioning
confidence: 99%
“…The aims of this study were to assess the frequency of the RAD51 / G135C (rs1801320), ATM / P1054R (rs1800057) and CHEK2 / T470C (rs17879961) polymorphisms and their putative association with the CAs, along with the evaluation of the health of 114 GSWs in Rio de Janeiro. The polymorphisms RAD51/G135C , ATM/P1054R , and CHEK2 / T470C were selected because they were associated with many cancers, such as prostate, breast, head and neck cancer, and leukemias (Skasko et al 2009 ; Schumacher et al 2018 ; Zeng et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%